Microbial dynamics and interactions in the spermosphere - Nelson, E.B (Annual review of phytopathology, 2004)
▪ Abstract  The spermosphere represents a short-lived, rapidly changing, and microbiologically dynamic zone of soil surrounding a germinating seed. It is analogous to the rhizosphere, being established largely by the carbon compounds released into the soil once the seed begins to hydrate. These seed exudations drive the microbial activities that take place in the spermosphere, many of which can have long-lasting impacts on plant growth and development as well as on plant health. In this review, I discuss the nature of the spermosphere habitat and the factors that give rise to its character, with emphasis on the types of microbial activities in the spermosphere that have important implications for disease development and biological disease control. This review, which represents the first comprehensive synthesis of the literature on spermosphere biology, is meant to illustrate the unique nature of the spermosphere and how studies of interactions in this habitat may serve as useful experimental models for testing hypotheses about plant-microbe associations and microbial ecology.